The costs and benefits of short sale disclosure - Duong, Truong X.; Huszár, Zsuzsa R.; Yamada, Takeshi (Journal of Banking & Finance, 2015)
In this study, we examine the impact of a market-wide mandatory disclosure policy on short selling on the Tokyo Stock Exchange. We find that average short selling slightly declined while investors’ shorting strategies changed significantly in response to the disclosure. Previously highly shorted stocks were shorted less and shorting activity shifted toward smaller and riskier stocks, suggesting that retail investors became the more likely short sellers. Short sales became more trend-chasing, prices became less informative, and short-term price volatility increased. Overall, the pricing efficiency benefits of short selling declined after the mandatory disclosure policy.